OPEN-KTH: An Open Lidar Dataset of KTH Campus Valhallavägen - Mohan, Naveen; Sainte Catherine, Maxime (Royal Institute of Technology, 2021)
OPEN-KTH: An open Lidar dataset of KTH campus Valhallavägen

Open-KTH is a subproject of the AD-EYE testbed for Automated Driving and Intelligent Transportation Systems.

Learn more at https://www.adeye.se/open-kth or contact adeye@md.kth.se

The AD-EYE testbed is based on the design presented in the work :

Naveen Mohan, Martin Törngren, "AD-EYE: A Co-Simulation Platform for Early Verification of Functional Safety Concepts", SAE Technical Paper 19AE-0203/2019-01-0126, https://doi.org/10.4271/2019-01-0126

Preprint available at: https://arxiv.org/abs/1912.00448

Data collected by students of the group "AD-EYE on Road" in the capstone course of the Mechatronics Masters program using the AD-EYE platform.

Mapping using the collected data was performed by Maxime Sainte Catherine from the AD-EYE team.

The data around "Försvarshögskolan", the Swedish Defence Academy, has been intentionally removed. As of 09-09-2021, there is no intention of restoring this missing data due to lack of legal clarity on what is publishable about this building.
Keywords: Electrical Engineering, Electronic Engineering, Information Engineering; Elektroteknik och elektronik